Keris Siamang Tunggal Alih Wahana Film Upin & Ipin: Representasi Identitas Budaya dan Nilai Pendidikan dalam Teater Pendidikan - Basri, Syaiful Qadar; Yanuartuti, Setyo (Jurnal Pendidikan Sendratasik, 2025)
This article explores the educational theater adaptation of the film Upin & Ipin: Keris Siamang Tunggal by students of the Sendratasik Education Study Program at Universitas Negeri Surabaya. Using a qualitative-descriptive method, the study analyzes how this adaptation communicates cultural identity and educational values to a student audience. The theatrical adaptation, developed as a final project for the "Teater Pendidikan course," highlights local wisdom, multiculturalism, and character education. By examining the process and performance during the implementation of Phase D in the course, this paper illustrates how educational theater serves as a medium of learning, value transformation, and identity reinforcement in performing arts education.